2016
DOI: 10.1073/pnas.1610994113
|View full text |Cite
|
Sign up to set email alerts
|

MYC-nick promotes cell migration by inducing fascin expression and Cdc42 activation

Abstract: MYC-nick is a cytoplasmic, transcriptionally inactive member of the MYC oncoprotein family, generated by a proteolytic cleavage of full-length MYC. MYC-nick promotes migration and survival of cells in response to chemotherapeutic agents or withdrawal of glucose. Here we report that MYC-nick is abundant in colonic and intestinal tumors derived from mouse models with mutations in the Wnt, TGF-β, and PI3K pathways. Moreover, MYC-nick is elevated in colon cancer cells deleted for FBWX7, which encodes the major E3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…MYC belongs to a family of transcription factors that regulates the expression of a large number of target genes, controlling almost every aspect of cell proliferation, differentiation, and metabolism. MYC promotes cell migration and invasion, for example by activating Rho GTPases 39 , but can also display anti-migratory effects through repression of CCL5/RANTES 40 . Since MYC enhances the promoter activity of CXCR4 41 , we examined whether Cxcr4b can act down-stream of myca in the zebrafish pronephros repair model.…”
Section: Discussionmentioning
confidence: 99%
“…MYC belongs to a family of transcription factors that regulates the expression of a large number of target genes, controlling almost every aspect of cell proliferation, differentiation, and metabolism. MYC promotes cell migration and invasion, for example by activating Rho GTPases 39 , but can also display anti-migratory effects through repression of CCL5/RANTES 40 . Since MYC enhances the promoter activity of CXCR4 41 , we examined whether Cxcr4b can act down-stream of myca in the zebrafish pronephros repair model.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, MYC-nick regulates cancer cell migration by enhancing the expression of fascin1 and subsequently promoting the stabilization of actin filaments. 39 Here, we found that LIF and CHIR99021 significantly enhanced fascin1 expression in mESC.…”
Section: Discussionmentioning
confidence: 55%
“…Interestingly, we observed that although c‐Myc expression was downregulated in OE cells, the JNK inhibitor increased the expression of c‐Myc. c‐Myc has been shown to be a protooncogene that modulates numerous cancer cell behaviors, including proliferation, differentiation, migration, and genomic instability . Recently, Ma et al demonstrated that c‐Myc also suppressed cell migration in Drosophila and human lung adenocarcinoma cell lines in a JNK‐dependent manner .…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc has been shown to be a protooncogene that modulates numerous cancer cell behaviors, including proliferation, differentiation, migration, and genomic instability. [33][34][35] Recently, Ma et al demonstrated that c-Myc also suppressed cell migration in Drosophila and human lung adenocarcinoma cell lines in a JNK-dependent manner. 36 Consistent with the results of that research, our results indicated that suppressed JNK activity was positively correlated with c-Myc expression.…”
Section: Discussionmentioning
confidence: 99%